2014
DOI: 10.1111/j.1532-950x.2014.12217.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Wound Healing Complications After Wide Excision of Injection Site Sarcomas of the Trunk of Cats

Abstract: An increased duration of surgery as the consequence of complex surgical procedures represented the best predictor for the development of WHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
3
20
0
1
Order By: Relevance
“…In small animal oncology, especially when dealing with feline ISS, the use of advanced imaging techniques in the pre-surgical setting has recently increased, but their use is still not a rule, and it is mostly left to surgeon choice. 4,7,9,15,16 In this study, tumour dimensions, both length and width, evaluated by CT showed a tendency towards being larger than the dimensions measured with calipers, consistent with previous reports. 13,16,17 In addition, in a proportion of cats, the shapes retrieved by the two methods demonstrated discrepancies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In small animal oncology, especially when dealing with feline ISS, the use of advanced imaging techniques in the pre-surgical setting has recently increased, but their use is still not a rule, and it is mostly left to surgeon choice. 4,7,9,15,16 In this study, tumour dimensions, both length and width, evaluated by CT showed a tendency towards being larger than the dimensions measured with calipers, consistent with previous reports. 13,16,17 In addition, in a proportion of cats, the shapes retrieved by the two methods demonstrated discrepancies.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, tumour dimensions, both length and width, evaluated by CT showed a tendency towards being larger than the dimensions measured with calipers, consistent with previous reports . In addition, in a proportion of cats, the shapes retrieved by the two methods demonstrated discrepancies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…If performed after the sterile scrub, the person administering the block would wear sterile gloves BOX 3 Technique for general tissue infiltration ▪ Technique: The nerve endings in the tissues are blocked by injecting the drug around or directly into the incision or wound 'field'. See more on the injection technique for BLIS in Part 1 (Abrão et al, 2014;Baxter, Bramlett, One, & Daniels, 2013;Cantatore et al, 2014;Waite, Gilliver, Masterson, Hardman, & Ashcroft, 2010).…”
Section: Critical Point For Oral Blocks: Excessive Mouth Openingmentioning
confidence: 99%